1990
DOI: 10.1177/106002809002400902
|View full text |Cite
|
Sign up to set email alerts
|

Increased 6-Hydroxycortisol Excretion in Pregnant Women: Implication of Drug-Metabolizing Enzyme Induction

Abstract: The effect of pregnancy on hepatic drug-metabolizing enzyme activity was investigated in nine healthy pregnant women using the ratio of 6-hydroxycortisol (6-OHF), to total 17-hydroxycorticosteroid (17-OHCS) in 24-hour urine as an index of the hepatic monooxygenase activity. The values of 6-OHF and the ratio (713 +/- 250 micrograms/d and 0.323 +/- 0.242; mean +/- SD) before delivery were significantly higher than they were during early puerperium (395 +/- 145 micrograms/d and 0.114 +/- 0.055) and approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…In this population, we found that the oral clearance of MDZ is significantly increased during pregnancy , suggesting that hepatic and/or intestinal CYP3A activity is increased during pregnancy. This conclusion is supported by other data in the literature that also suggest increased CYP3A activity during human pregnancy (Rey et al, 1979;Ohkita and Goto, 1990;Kosel et al, 2003;Tracy et al, 2005). The discrepancy between humans and macaques may be due to differences in the intrinsic rate of MDZ metabolism in the two species.…”
Section: Discussionsupporting
confidence: 81%
“…In this population, we found that the oral clearance of MDZ is significantly increased during pregnancy , suggesting that hepatic and/or intestinal CYP3A activity is increased during pregnancy. This conclusion is supported by other data in the literature that also suggest increased CYP3A activity during human pregnancy (Rey et al, 1979;Ohkita and Goto, 1990;Kosel et al, 2003;Tracy et al, 2005). The discrepancy between humans and macaques may be due to differences in the intrinsic rate of MDZ metabolism in the two species.…”
Section: Discussionsupporting
confidence: 81%
“…However, pregnancy is associated with many physiological changes, which may have an impact on the pharmacokinetics of drugs 15,16. Thus, it is of value to study the pharmacokinetic properties of antimalarial drugs in this special group of patients to determine whether adjustment of dose or dose regimen is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Other evidence suggesting a hormonal influence on CYP3A activity exists in pregnancy. 6β‐hydroxycortisol:cortisol ratios have been found to increase 300% in the third trimester of pregnancy and return to baseline within 3 months after delivery [9].…”
Section: Introductionmentioning
confidence: 99%